Pelvic rocking exercise sebagai alternatif manajemen nyeri dysmenorrhea primer: A systematic literature review - Kirana, Magenta; Fauza, Sri Novia (Holistik Jurnal Kesehatan, 2026)
Background: Primary dysmenorrhea is a common menstrual disorder experienced by adolescent girls and young women of reproductive age, characterized by lower abdominal cramping pain that interferes with daily activities without any underlying organic pathology. Pelvic rocking exercise is a potential non-pharmacological intervention because it is simple, inexpensive, and can be performed independently; however, the scientific evidence is still scattered and has not been systematically synthesized. Purpose: To evaluate pelvic rocking exercise as an alternative for managing pain in primary dysmenorrhea. Method: A systematic review was conducted by searching literature in PubMed, Scopus, and Google Scholar databases using keywords related to "pelvic rocking exercise" and "primary dysmenorrhea" within the 2020–2026 period. Results: A total of 10 studies met the inclusion criteria (experimental or quasi-experimental designs) and were analyzed narratively due to high heterogeneity among studies. Pelvic rocking exercise consistently showed effectiveness in reducing menstrual pain intensity from moderate–severe to mild or no pain through mechanisms such as pelvic muscle relaxation, improved blood circulation to the uterus, and the release of natural endorphins, with no reported side effects. This intervention also improved comfort and the ability to perform daily activities during menstruation. Conclusion: Pelvic rocking exercise is effective in reducing the intensity of dysmenorrhea pain and can be considered a safe, practical, and easily self-administered non-pharmacological therapy.   Keywords: Adolescent; Non-Pharmacological Pain Management; Pelvic Rocking Exercise; Primary Dysmenorrhea.   Pendahuluan: Dismenore primer merupakan gangguan menstruasi yang umum dialami remaja putri dan wanita usia reproduktif awal, ditandai nyeri kram abdomen bawah yang mengganggu aktivitas sehari-hari tanpa adanya patologi organik. Pelvic rocking exercise menjadi salah satu intervensi non-farmakologi yang potensial karena sederhana, murah, dan dapat dilakukan mandiri, namun bukti ilmiahnya masih tersebar dan belum tersintesis secara sistematis. Tujuan: Untuk mengevaluasi pelvic rocking exercise sebagai alternatif manajemen nyeri dismenore primer. Metode: Tinjauan sistematis dilakukan dengan pencarian literatur pada database PubMed, Scopus, dan Google Scholar menggunakan kata kunci terkait "pelvic rocking exercise" dan "primary dysmenorrhea" pada rentang tahun 2020–2026. Hasil: Terdapat 10 studi yang memenuhi kriteria inklusi (desain eksperimental atau quasi-eksperimental) dianalisis secara naratif karena heterogenitas tinggi antarstudi, Pelvic rocking exercise secara konsisten efektif mengurangi intensitas nyeri haid dari tingkat sedang-berat menjadi ringan atau tidak ada nyeri melalui relaksasi otot panggul, peningkatan sirkulasi darah ke uterus, dan pelepasan endorfin alami, tanpa efek samping yang dilaporkan. Intervensi ini juga meningkatkan kenyamanan dan kemampuan beraktivitas selama menstruasi. Simpulan: Pelvic rocking exercise efektif mengurangi intensitas nyeri dismenore dan dapat menjadi alternatif terapi non-farmakologis yang aman, praktis, dan mudah dilakukan secara mandiri.   Kata Kunci: Dismenore Primer; Manajemen Nyeri Non-Farmakologi; Pelvic Rocking Exercise; Remaja.